2011
DOI: 10.1111/j.1461-0248.2011.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest species diversity reduces disease risk in a generalist plant pathogen invasion

Abstract: Empirical evidence suggests that biodiversity loss can increase disease transmission, yet our understanding of the 'diversity-disease hypothesis' for generalist pathogens in natural ecosystems is limited. We used a landscape epidemiological approach to examine two scenarios regarding diversity effects on the emerging plant pathogen Phytophthora ramorum across a broad, heterogeneous ecoregion: (1) an amplification effect exists where disease risk is greater in areas with higher plant diversity due to the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
143
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 49 publications
8
143
0
4
Order By: Relevance
“…Loss of biodiversity might have extensive, positive or negative, impacts on disease transmission in natural ecosystems (Borer et al 2009, Haas et al 2011. Our study showed that tree diversity plays a role in biotrophic fungal pathogen infections of common European forestry species.…”
Section: Discussionmentioning
confidence: 93%
“…Loss of biodiversity might have extensive, positive or negative, impacts on disease transmission in natural ecosystems (Borer et al 2009, Haas et al 2011. Our study showed that tree diversity plays a role in biotrophic fungal pathogen infections of common European forestry species.…”
Section: Discussionmentioning
confidence: 93%
“…Although an increasing number of studies have reported negative correlations between host diversity and disease risk (29,38,39), the hidden effects of concurrent changes in parasite communities have rarely been explored (19,31,40). Future studies examining the biodiversity-disease relationship should focus more heavily on the relative importance of multiple components of biodiversity (and how they covary) in driving observed patterns in disease risk (41)(42)(43), including the direct and indirect effects of hosts, nonhosts (e.g., predators and competitors), parasites, as well as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, because we expected host diversity, parasite diversity, and parasite load to correlate in the field owing to links between colonization and diversity, we used an experimental approach first in the laboratory and then in seminatural outdoor mesocosms to decouple the unique effects of each form of diversity on infection by Ribeiroia and the total parasite community. While building upon previous efforts examining the individual effects of host and parasite richness in isolation (15,19,(27)(28)(29)(30), this study combines cross-sectional coinfection data, field-based measurements of transmission, and new experiments to explicitly examine the effects of host species richness on infection by an entire parasite assemblage, thereby mechanistically evaluating the joint effects of host and parasite diversity on disease risk.…”
Section: Significancementioning
confidence: 99%
“…Disease dilution, an important ecosystem service, has been reported for a variety of systems from vectorborne zoonoses (i.e. diseases transmitted from animals to humans) to directly transmitted plant pathogens [16,[18][19][20][21][22]. However, a variety of mechanisms might underlie this common pattern, and the effects of biodiversity on disease prevalence are still in debate [23][24][25].…”
Section: Introductionmentioning
confidence: 99%